Producing Green Concrete with Plastic Waste and Nano Silica Sand - Qasim, M. F.; Abbas, Z. K.; Abed, S. K. (Engineering, Technology & Applied Science Research, 2021)
Industrial and urban development has resulted in the spread of plastic waste and the increase in the emissions of carbon dioxide resulting from the cement manufacturing process. The current research aims to produce green (environmentally friendly) concrete by using plastic waste as coarse aggregates in different proportions (10% and 20%) and nano silica sand powder as an alternative to cement in different proportions (5% and 10% by weight). The results showed that compressive strength decreased by 12.10% and 19.23% for 10% and 20% plastic waste replacement and increased by 12.89% and 20.39% for 5% and 10% silica sand replacement respectively at 28 days. Flexural strength decreased by 12.95% and 19.64% for 10% and 20% plastic waste replacement and increased by 11.16% and 19.86% for 5% and 10% silica sand replacement. Splitting tensile strength decreased by 12.74% and 20.22% for 10% and 20% plastic waste replacement and increased by 10.86% and 19.66% for 5% and 10% silica sand replacement. Dry density decreased by 4.51% and 7.83% for 10% and 20% plastic waste replacement and increased by 2.78% and 4.10% for 5% and 10% silica sand replacement respectively at 28 days.